Dietary intake and adequacy of energy and nutrients in Mexican adolescents: Results from Ensanut 2012 - Elsa B Gaona-Pineda; Fabiola Mejía-Rodríguez; Lucía Cuevas-Nasu; Luz M Gómez-Acosta; Eduardo Rangel-Baltazar; Mario E Flores-Aldana (Instituto Nacional de Salud Pública, 2018)
Objective. To estimate energy and nutrient intakes and adequacies in Mexican adolescents. Materials and methods. Dietary intake was assessed in 1 961 adolescents who participated in the National Health and Nutrition Survey 2012 (Ensanut 2012), by a food frequency questionnaire. Medians of intakes and adequacies were estimated for energy, macroand  micronutrients and are presented by residence area, region and household wealth index (HWI). Consumption by food groups was estimated. Results. Median daily energy intake was 2 000 Kcal in males and 1 800 Kcal in females. High prevalences of inadequacy were observed for fiber, PUFAs, iron, zinc and calcium. These inadequacies were higher among individuals of low HWI. Moreover, excessive intakes of total and saturated fat were higher among adolescents of higher HWI. Conclusion. The diet of Mexican adolescents is deficient in essential nutrients for good health and high in saturated fat. Actions are needed to promote a healthy diet.